Challenges and Choices in Prostate Cancer Irradiation: From the Three Dimensional Conformal Radiotherapy to the Era of Intensity Modulated, Image-Guided and Adaptive Radiation Treatment - Kalogeridi, Maria-Aggeliki; Kyrgias, George; Zygogianni, Anna; Kouvaris, John; Theodorou, Kyriaki; Kelekis, Nikolaos; Kouloulias, Vassilios (Urology Journal, 2014)
In the last decades the status of radiotherapy was tremendously increased in terms of conformity to the target as well as image-guided techniques in conjunction with intensity-modulated radiotherapy (IMRT). The technological improvement had a significant clinical outcome for better response and lower toxicity to the surrounding normal tissues. Nowadays the incidence of rectal toxicity has been significantly decreased, especially with image guided radiation therapy (IGRT), whereas the dose escalation to the prostate has driven the clinical practice to the fact that radical radiotherapy for low or intermediate risk prostate cancer is definitely equivalent to surgery. The treatment volume can be reduced by reducing the size of the necessary margins to count for inaccuracies in target position and patient setup. This can be achieved either by improving the daily localization of the target before treatment or by adapting the treatment in response to feedback. This is the goal of image-guided and adaptive radiotherapy, respectively. These techniques improve the accuracy of dose delivery with a significant impact on clinical outcome and toxicity.